Os discursos sobre o trabalho em O Retrato de Érico Veríssimo - Bruneti, Marcio (2014)
This dissertation analyzes the discursive constructions on work in the novel O Retrato (―The Portrait‖) (2003), by Erico Verissimo, from a multidisciplinary perspective. Discourses on work in O Retrato are elements of a historical panel from which the author does a critical reading of the society of his time. The aim of this research is to present this process. The discourses are taken as the artist‘s own formulation in a certain socio-historical context, to which multiple voices concur and were introduced in the novel through the speeches of the narrator, the characters, the intertwined genres as advocated by Bakhtin (1988). In this study, these discourses are analyzed from a concept of work as a human activity in connection to the environment, which is fundamental in the process of constitution of the social being, that is, in its ontological meaning. In the novel‘s context, this understanding is related to the historical interactions of the relations between free work/slave work; of the perception process, by the rural man, of the separation between work and land property; of the unique combination, in Rio Grande do Sul, of diverse human elements in the constitution of a ―work culture‖ and the absence of a work tradition related to the guilds and hanses, such as in the pre-capitalist Europe. The social differences, the telluric element, the role of the extensive family as a socio-productive unit and the relations that were characteristics of a society rooted in the rule of the favor are aspects present in the discourses around work that compose the Érico Veríssimo‘s criticism in the novel. As to the methodological procedures, it is a bibliographical research, in which the quantitative analysis is applied to the treatment of data extracted from the numbers provided by Chaves (1979) and Carpeaux (1979), with the aim to locate the work in the author‘s literary production context. We must consider that the novel was published at the top of Érico Veríssimo‘s career as the second book of a trilogy of which the initial part was a great success with the public and the critics, generating expectations that were eventually not met: one of the author‘s less popular novels, O Retrato had a fundamental role in the set formed by O Tempo E O Vento (―Time and the Wind‖) as in its pages Érico portrays an environment of degradation of those values that were representative of the people of Rio Grande and that constitutes the great criticism of his work. The discourses on work in the novel are aligned with this great project, as we sought to show here, either in the difference of perspective when considering the work as a mission received as a legacy versus the burden of duty, either through the valuation of the ideals of the telluric being in contrast with the values of the emerging bourgeois capitalist society, through the permanence of favor relations centered around the character Rodrigo Cambará, which is a mechanism that preserves the game of the socio-political scene, despite the changes taking place in the economic-productive field; or by this character‘s trajectory, whose values and ideals degenerate.